{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Stitz-Zeager_College_Algebra_e-book

Both ways are demonstrated in the following example

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: + , f (x) → −∞ Slant asymptote: y = −x As x → −∞, f (x) → ∞ As x → ∞, f (x) → −∞ (l) f (x) = y 7 6 5 4 3 2 1 −6 −5 −4 −3 −2 −1 −1 −2 −3 −4 −5 −6 −7 1 2 3 4 5 6 x x x 4.2 Graphs of Rational Functions x2 − 2x + 1 x3 + x2 − 2x Domain: (−∞, −2) ∪ (−2, 0) ∪ (0, 1) ∪ (1, ∞) x−1 f (x) = , x=1 x(x + 2) No x-intercepts No y -intercepts Vertical asymptotes: x = −2 and x = 0 As x → −2− , f (x) → −∞ As x → −2+ , f (x) → ∞ As x → 0− , f (x) → ∞ As x → 0+ , f (x) → −∞ Hole in the graph at (1, 0) Horizontal asymptote: y = 0 As x → −∞, f (x) → 0− As x → ∞, f (x) → 0+ 265 (m) f (x) = y 5 4 3 2 1 −5 −4 −3 −2 −1 1 2 3 4 −1 −2 −3 −4 −5 y 1 x−2 1 Shift the graph of y = x to the right 2 units. 4. (a) f (x) = 3 2 1 −1 1 2 3 4 5 x −1 −2 −3 3 x 1 Vertically stretch the graph of y = x by a factor of 3. 3 Reﬂect the graph of y = x about the x-axis. 3 Shift the graph of y = − x up 1 unit. (b) g...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online